Influência de sistemas integrados de produção nas características físicas e químicas de um argissolo - Cruz, Diego Lima de Souza (2017)
The Crop-Livestock-Forest Integration System (ILPF) is considered one of the most suitable conservationist systems for the recovery of degraded pastures, because it increases the efficiency of the area utilization. In this context, the present work was elaborated with the objective of comparing the management systems with a natural forest with the physical and chemical characteristics of Ultisol in the state of Roraima. The study was carried out in a private property with ILPF experiment installed in partnership with Embrapa-RR. There were 4 main treatments (Areas): T1 = Rotated Pasture; T2 = Natural Forest (NF); T3 = Crop-Livestock Integration (CLI); T4 = Livestock-Forest Integration (LFI); The secondary treatments were 6 depths: P1 = 0 to 10 cm; P2 = 10 to 20 cm; P3 = 20 to 40 cm; P4 = 40 to 60 cm; P5 = 60 to 80 cm; P6 = 80 to 100 cm in a completely randomized design in the spli-plot scheme. The evaluated properties were: Soil Penetration Resistance (PR), Texture, Soil Density (SD) and Soil Particle Density (PD), Total Porosity (TOP), Dispersed Clay in Water (DCW), Clay Flocculation Degree (CFD) , Soil Organic Matter (SOM), Soil Carbon Stock (SCS) and Soil Physic Quality Index (SPQI). Analyzing the set of all the properties and comparing the managed environments with the natural forest, considered as a parameter of physical soil quality, it was verified that there is no physical degradation of the soil in the management systems studied, being able to be indicated to be used as a recovery system for degraded areas. The high SD values in the CLI and LFI was a signal to the importance of implementing a physical soil quality monitoring program in the property, besides the control in the activities of machines and animals in those systems.